The effect of partial substitution of Moringa oleifera leaf meal on the relative growth performance and incidence of scours in piglets. Issue 1 (31st December 2022) - Chikasa, Bright; Shoniwa, Andrew; Mangwiro, Clement; Dhliwayo, Marshall; Tinashe Tekedza, Trevor
Abstract : The effect of Moringa oleifera leaf meal (MOLM) as a scour prophylaxis and on growth parameters of piglets was evaluated. A total of 168 piglets from 15 litters were cross fostered and randomly assigned to three dietary treatments; 0% MOLM (control diet), 4.5% MOLM and 8% MOLM inclusion test diets. The feed conversion ratio (FCR), average daily gain (ADG), body weight (BW) and average daily feed intake (ADFI) and faecal viscosity (FV) were measured. The effect of MOLM inclusion level on FCR, ADG, BW, ADFI and FV was analysed using PROC GLM of SAS. Dietary inclusion of 4.5% MOLM significantly reduced the ADFI of piglets when compared to 0% MOLM, however 8% MOLM had higher ADFI than either 0% or 4.5% MOLM inclusion. There was no effect of MOLM dietary inclusion on ADG; however 8% MOLM dietary inclusion had a higher FCR when compared to 0% or 4.5% MOLM. Piglets in control treatment (0% MOLM) had more incidence of scours than 8% MOLM diet and did not differ from 4.5% MOLM. There was no effect in faecal viscosity between 4.5% and 8% MOLM diets. MOLM dietary inclusion significantly reduced the cost per kilogram weight gain. It was concluded that MOLM can replace soya bean meal up to 4.5% in piglet creep diets.